Regia e romanzo: Una questione storiografica alla prova dei fatti - Marchetti, Marta (Mimesis Journal, 2020)
This essay discusses the historiographic assumption put forward by Jean-Pierre Sarrazac in a 2005 study, which considers the appearance of the modern director as ensuing from a common novel and theater culture. Starting from the theoretical- methodological approach proposed by the French scholar, we aim at assessing its developments outside of the case study in hand, by measuring its procedural scope and its evolution over time. We will try to understand if André Antoine’s statement, explaining in 1903 that the director's work matched the describing of the novelist, was still valid a few years later when, also in Paris, Jacques Copeau worked on Dostoevsky's Brothers Karamazov.